The assessment of intellectual capital in Polish regions - Bronisz, Urszula; Heijman, Wim; van Ophem, Johan (Applied Studies in Agribusiness and Commerce, 2012)
In a knowledge-based economy intangible assets are indispensable to achieve competitive advantages. Resources like intellectual capital are perceived as crucial factors especially for regional growth. Intellectual capital is comprehended as a multidimensional concept, defined and explained in many various ways, depending on the context and further application. The purposes of this article is to consider the role and importance of the intellectual capital for regional development and competitiveness and to try to use it for an estimation of regional advance progress. On the basis of literature review the article provides a framework to analyse the intellectual capital and its main components. The central attention of the paper focuses on the evaluation of the intellectual capital in Polish regions and its influence on regional performance. The paper surveys the empirical examination of 16 Polish regions in terms of intellectual capital and simultaneously assesses the level of intellectual capital in rural areas. The article provides the insight into the role and value of the intellectual capital in Polish regions.